The Relationship Between Self-Disclosure and Anonymity in Online Social Media Users - Laila Nur Maghfiroh; Amri Hana Muhammad (Journal of Social and Industrial Psychology, 2024)
The more widespread the use of social media, the easier it is for individuals to disclose themselves (self disclosure). One of the factors that influence self disclosure is personality which plays a role in shaping a person's behavior on social media, including behavior to present themselves anonymously. These factors cause the phenomenon of anonymity in social media. This study aims to determine the correlation between self disclosure and anonymity in online social media users. This study uses quantitative methods with correlation techniques. The population of this study are active users of anonymous accounts on social media. The sampling technique for this study is incidental sampling. The amount of samples obtained was 184 people. The self disclosure scale uses the Revised Self-Disclosure Scale (RSDS) consists of 14 items adopted from Nugroho (2018) based on the theory developed by Leung (2002). The anonymity scale consists of 14 items adopted from Chairunnisa (2018) based on the scale compiled by Lee et al. (2013). The reliability coefficient of the self disclosure scale is 0.808 and the reliability coefficient of the anonymity scale is 0.855. Hypothesis testing was carried out with the pearson product moment correlation test and resulted a significance value of 0.727. This means that there is no relationship between self disclosure and anonymity in online social media users. Further research is suggested to examine more specifically based on one type of social media